Improving the Cultural Competency of Midwives on Maternal and Child’s Health Services in Sa'dan North Toraja - Weny Lestari (IPTEK Journal of Proceedings Series, 2020)
Maternal and neonatal deaths, and delivery’s coverage at healthcare still be problems in North Toraja. Culture was one of factors that influence unsafe delivery. It’s important for midwives to understand culture in community. The objectives of this study were to improve midwives’ cultural competency and to minimalize cultural barriers. Cultural competency had been trained to 19 midwives in Sa’dan North Toraja. Training contained material of the culture of pregnancy and childbirth. Through roleplay regarding cultural problems faced by midwives in community and how they learned from each other to find solutions to cultural barriers in their duties. Roleplay’s themes had been founded together contains about how to: (1) socialization to family member of traditional midwife (to 'mappakianak) that not allowed to help delivery; (2) convincing woman to deliver at healthcare; (3) minimize the gap between midwives and community; (4) convincing delivery decision making in extended family; (5) resolve problem of cultural role of mother in family, by involving, discussion and collaboration with parents, family members, and respectable community leaders. It concluded that improving cultural competency could minimalize cultural barriers in community. Communication between midwives and communities were the key of improvement maternal and child’s health services.